Alluvial stratification styles in a large, flash‐flood influenced dryland river: The Luni River, Thar Desert, north‐west India. Issue 1 (16th July 2018) - Carling, Paul A.; Leclair, Suzanne F.
Abstract: Detailed descriptions of the architecture of dryland‐river deposits are few, which hinders the understanding of stratigraphic development in aggradational settings. The aim of this study was to obtain new insight into the depositional dynamics and resultant stratigraphy of steep, high‐energy dryland rivers in particular. The study site is within the Luni River, the largest river in the Thar Desert, India. A 700 m wide section, 5 m deep, was logged and the dated‐stratification related to the flow regimen. Seasonal discharges may reach 14 000 m 3 sec −1 but the bed is usually dry. The deposits consist mainly of sandy upper‐stage plane bed lamination and low‐angle stratification deposited in supercritical flows with some strata showing gravel‐lense antidune signatures. Estimated hydraulic parameters indicate a dominance of the upper‐stage plane bed state. Less frequent dune trough cross‐sets occur at all depths, yet commonly as isolated sets with erosive upper boundaries. Localized deep scour causes slumping and soft‐sediment deformation. Scour holes adjacent to older bedded deposits are rapidly infilled, often by massive deposits. Repeated deep scour results in units of deposition of different ages (50 to 500 a bp ) and different facies found at similar shallow depths (2 to 3 m). Older dates (1 to 2 ka bp ) occur in lower strata (4 to 5 m depths) at which depths younger units also are preserved locally. The steep, high‐energy depositional environment promotes the unusual preservation and predominance of upper‐stage facies, in contrast to a relative paucity of lower‐stage facies. Frequent local deep‐scour during floods means that specific facies rarely can be traced across the river channel for more than a few metres, but are replaced by other facies in close proximity. These results should help interpretation of high‐energy sediment deposits widely and improve understanding of the stratigraphic development in modern dryland rivers, and in characterizing oil, gas and groundwater reservoirs in the dryland geological record more generally.